Resistensi Perempuan terhadap Perjodohan dalam Lirik Lagu Kontemporer Berbahasa Madura: Kajian Futurologi Etnofeminis - Masyithah Maghfirah Rizam; Darni Darni; Suyatno Suyatno (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This study explores the representation of female resistance to arranged marriage in contemporary Madurese song lyrics. The analysis focuses on three songs: Benni Peleyan Bula (2014) by Yuli Asiska, Mateh Rassa (2022), and Mile Reng Towah (2024) by Ahmed Habsy. Using a qualitative approach with ethnofeminism and literary futurology as analytical frameworks, the findings reveal that resistance does not always appear as direct defiance but is expressed through forms such as active resignation, emotional disappointment, and reflective awareness. These expressions signify a shift in cultural values and the emergence of new social imaginaries within Madurese society. Song lyrics serve not only as entertainment but also as symbolic spaces where women negotiate identity, express dissent, and envision a more gender-equitable future. Through emotional narratives, these songs project alternative cultural futures where women possess greater autonomy in choosing their life partners and defining their own happiness.